Variability, Heritability and Genetic Advance Analysis in Bread Wheat (Triticum Aestivum L.) Genotypes in Northwestern Ethiopia - Ferede, Misganaw; Worede, Fisseha (International Journal of Sustainable Agricultural Research, 2020)
Studies on degree of genetic advance as well as rate of genetic progress in grain yield and yield associated traits in bread wheat genotypes over years are limited. Therefore, this study was initiated to explore genetic advance and rate of genetic progress over years in bread wheat breeding program. Twelve bread wheat genotypes released in between 1995-2012 were used as experimental treatments. The experimental treatments were laid out on randomized complete block design with three replications across locations over years. The study was conducted at Adet, Debretabor, Finoteselam, Injibara and Simada in 2014 and 2015 cropping seasons. The traits grain yield, biological yield, spike length, number of seeds per spike and thousand seed weight showed medium genetic and phenotypic variation, higher heritability and medium genetic advance to the mean of the population whereas days to physiological maturity, plant height, and test weight showed negligible in both genotypic and phenotypic variation, higher heritability and negligible genetic advance to the mean of the population. In the genetic advance analysis over years, only thousand seed weight showed positive significant increment while grain yield, biological yield, days to physiological maturity, plant height and test weight showed positive non-significant increment. Meanwhile spike length and number of seeds per spike showed negative non-significant decrement over 18 years. Therefore, breeders should be considered the yield related traits to bring the desired genetic enhancement as well as to develop demanded genotypes in the future bread wheat breeding investigations.